2022
DOI: 10.2217/fon-2021-0818
|View full text |Cite
|
Sign up to set email alerts
|

Role of Adjuvant Chemotherapy After Concurrent Chemoradiotherapy in Patients With Locally Advanced Cervical Cancer

Abstract: Objectives: With the use of concurrent chemoradiotherapy (CCRT) for locally advanced cervical cancer (LACC), survival outcomes are still not optimal. This study was designed to evaluate the efficacy and safety of adjuvant chemotherapy (ACT) for patients with LACC after treatment with CCRT. Methods: Patients diagnosed with stage IIA-IIIB LACC, were retrospectively analyzed. All patients received cisplatin-based CCRT and were divided into two groups: ACT after CCRT (CCRT + ACT group) and observation after CCRT (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, Kou et al ( 2022 ) disagreed with this view because they found that adjuvant chemotherapy was not beneficial for the prognosis of patients and possibly led to a higher risk of side effects. A prospective study (NCT02036164) (Tangjitgamol et al 2019 ; Tovanabutra et al 2021 ) also indicated that adjuvant chemotherapy in combination with concurrent chemoradiotherapy could not improve the response rate or survival benefits of patients with LACC without para-aortic lymph node enlargement.…”
Section: Discussionmentioning
confidence: 99%
“…However, Kou et al ( 2022 ) disagreed with this view because they found that adjuvant chemotherapy was not beneficial for the prognosis of patients and possibly led to a higher risk of side effects. A prospective study (NCT02036164) (Tangjitgamol et al 2019 ; Tovanabutra et al 2021 ) also indicated that adjuvant chemotherapy in combination with concurrent chemoradiotherapy could not improve the response rate or survival benefits of patients with LACC without para-aortic lymph node enlargement.…”
Section: Discussionmentioning
confidence: 99%
“…However, Kou et al 24 disagreed with this view because they found that adjuvant chemotherapy was not bene cial for the prognosis of patients and possibly led to a higher risk of side effects. A prospective study (NCT02036164) 25 26 also indicated that adjuvant chemotherapy in combination with concurrent chemoradiotherapy could not improve the response rate or survival bene ts of patients with LACC without para-aortic lymph node enlargement.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that different clinical stages are associated with varying prognostic outcomes, with 5-year survival rates of approximately 92%, 65%, and 17% for early-stage, locally advanced, and metastatic cervical cancer, respectively (5,6). Despite receiving platinum-based concurrent chemoradiotherapy (CCRT) followed by intracavitary brachytherapy (7), nearly 40% of patients with locally advanced cervical cancer (LACC) still experience poor outcomes such as recurrence and metastasis (8,9). Currently, there is a lack of ideal treatment methods for recurrence or metastasis (10).…”
Section: Introductionmentioning
confidence: 99%